Adsorption of Methylene Blue by Magnetic Activated Carbon/Chitosan Composites Prepared from Spent Coffee Grounds - Iliya Kartika Santosa; Meta Fitri Rizkiana (JOBC, 2023)
Spent coffee grounds were used as the main ingredient for composing magnetically activated carbon/chitosan (MACC) composites and synthesized using the coprecipitation method. The SEM-EDX characterization was used to understand the elemental identification and morphology of the adsorbent before the MACC was applied to remove methylene blue (MB) from the aqueous solution. Magnetic activated carbon/chitosan was fabricated under the following circumstances: the molar ratio of ferrous/ferric ions was 2:1, and the coprecipitation temperature was 60 °C for five hours. Adsorption parameters for MB were investigated. The adsorption by MACC was evaluated thermodynamically for the discharge of MB from an aqueous solution as a function of temperature. Calculations of thermodynamic parameters were conducted. Batch adsorption experiments were operated at 308 K, 318 K, and MB concentration of 5-50 mg L-1 to investigate the adsorption behavior. According to the results, MACC has a porous structure. The adsorption process is more reactive upon raising the temperature, commonly known as endothermic. Based on R2 values, the adsorption of MB onto MACC was found to fit the Freundlich model best. The maximum adsorption capacity of the MACC was counted as 24.5 mg/g. The adsorption process is spontaneous, which was concluded from calculating thermodynamic parameters.